Characterization of the basement membrane in kidney renal clear cell carcinoma to guide clinical therapy - Xiong, Xi; Chen, Chen; Yang, Jun; Ma, Li; Wang, Xiong; Zhang, Wei; Yuan, Yuan; Peng, Min; Li, Lili; Luo, Pengcheng (Frontiers in Oncology, 2022)
Renal cell carcinoma (RCC) is the most common kidney cancer among adult cases, The most common histological subtype of RCC is kidney renal clear cell carcinoma (KIRC) with a dismal prognosis, accounting for more than 90% of patients. Numerous studies have demonstrated the importance of basement membrane genes (BMGs) in tumor growth. However, the significance and prognostic value of BMGs in KIRC remain unclear. We constructed prognostic models of BMGs characteristics. In TCGA cohort, patients' prognosis in the HRS group was poorer than that in the LRS group, which was verified in the GEO cohort. PCA results showed that the PRS model could effectively distinguish between the high-risk and low-risk groups. Clinicopathological features and HRS showed a positive correlation. Analysis of association between the PRS model and TME characteristics revealed higher levels of immune infiltration in the HRS group. The HRS group showed higher immune cell scores, stromal cell scores, and ESTIMATE values, indicating a higher immunological infiltration level in the HRS group. Predicting patients' response to chemotherapeutic agents for the treatment of kidney cancer, and chemoresistance to FR-180204, GSK1904529A, KIN001-102, and YM201636 was developed in the HRS group, while sensitivity to the other 27 chemotherapeutic agents was recorded. We further validated FREM2 expression on human kidney tissues and cell lines, which showed low expression of FREM2 in human renal cancer cell lines and tissues, and FREM2 expression level had a negative correlation with clinicopathological characteristics. Our study showed that BMGs were strongly associated with kidney cancer, and the risk scores related to the expression levels of 10 BMGs were assessed by survival status, TME, clinicopathological features, and resistance to chemotherapy. The above results suggested that FREM2 is expected to be a potential prognostic indicator for kidney cancer. Therefore, this study provides a valid predictive model and new therapeutic targets for the prognosis of kidney cancer as well as the clinical treatment, thus facilitating the development of individualized tumor therapy.